Faktor-Faktor yang Berhubungan dengan Melanjutkan Pendidikan terhadap Motivasi Belajar pada Mahasiswa Non-Reguler Program Studi Sarjana Keperawatan - Yunita Fitria Rejeki; Dinnar Kartinurmaya; Indra karana; Suparni Suparni (Jurnal Sehat Masada, 2023)
Background:. The desire to learn in non-regular students is different from regular students. In non-regular students, the reason for continuing education is because of the desire to gain experience and the government's recommendation to become a professional nurse. In the learning process, some students who have worked have difficulty managing learning time. Objective: Identifying factors related to continuing education on learning motivation in non-regular students of nursing undergraduate study programs. Method: Type of correlation quantitative research. With the formula used spearmant rank. With a population of 30 and a sample of 28. Research was conducted at STIKes Dharma Husada in June-July 2023. Research Results Internal factors found the results of 24 people (85.7%) were moderate, 3 people (10.7%) were low and 1 person (3.5%) was high. External factors are good 16 people (57.1%) and low 12 people (42.9%) Moderate learning motivation as many as 20 people (71.4%), low and high each 4 people (14.2%). The results obtained in the study are Ho is accepted for internal factors and Ha is accepted for external factors on learning motivation. Suggestion: Suggestion: to increase learning motivation in non-regular students, study groups can be formed. And there is further research on this research to be a reinforcement or comparison